Cost-effectiveness of modified fully oral 9-month treatment regimens for rifampicin-resistant tuberculosis in Belarus, Georgia, Kazakhstan and the Republic of Moldova - Allel, Kasim; Palmer, Tom; Abou Jaoude, Gerard Joseph; Korotych, Oleksandr; Yedilbayev, Askar; Vilc, Valentina; Corloteanu, Andrei; Macari, Mariana; Evghenia, Cula; Laticevschi, Dumitru; Shakhimurat-Shaimovich, Ismailov; Anar-Saduakasovna, Rakisheva; et al. (BMJ global health, 2025)
IntroductionPrior to 2020, treatment options for multidrug-resistant tuberculosis (MDR-TB) were limited and typically involved long treatment durations and high financial burdens. In the eastern European and central Asian (EECA) region, traditional inpatient tuberculosis (TB) care models, alongside high MDR-TB rates, escalate nosocomial transmission risks and treatment costs. Modified, fully oral, shorter treatment regimens (mSTR) implemented in the WHO European Region under operational research conditions offered a potential reduction in the burden of MDR-TB treatment for both patients and health systems.MethodsWe conducted the first regional evaluation of the cost-effectiveness of the novel mSTR treatment regimen compared with the standard of care (SOC) in Belarus, Georgia, Kazakhstan and Republic of Moldova. We used cohort data on mSTR efficacy and WHO data on SOC in patients with MDR-TB. We used a Markov model, with treatment costs calculated from the provider perspective. Outcomes were measured in quality-adjusted life years (QALYs), with incremental cost-effectiveness ratios (ICER) calculated per QALY gained in each country. An annual 3% discount rate was used for both costs and outcomes. We performed univariate and probabilistic sensitivity analysis (PSA) to assess the robustness of our cost-effectiveness calculations under varying assumptions. Finally, we estimated potential cost savings if mSTR was implemented nationally and we evaluated the incremental net monetary benefit (iNMB) and willingness-to-pay (WTP) thresholds based on Wood et al’s country-level cost-effectiveness thresholds. All costs were reported in 2022 USD.ResultsWe estimated that mSTR can reduce TB treatment costs by between 23% and 47% and drug costs by 39% to 74%, compared with SOC in the countries studied. mSTR resulted in cost savings of between $3596 and $8174 per patient and offered additional health gains of between 0.56 to 2.69 QALYs per patient. mSTR remained cost-effective (iNMB>0) compared with SOC in 78%, 85%, 91% and 92% of PSA simulations in Belarus, Georgia, Kazakhstan and Republic of Moldova, respectively, when compared with their country-level WTP threshold. Implementing mSTR in up to 80% of MDR/rifampicin-resistant TB patients may result in cost savings of $20.5, 2.5, 0.7 and 0.2 million in Kazakhstan, Belarus, Republic of Moldova and Georgia; equivalent to 17%, 3%, 4% and 1% of their national TB budgets, respectively.ConclusionsCompared with SOC, mSTR is a more cost-effective treatment option for MDR/RR-TB, which should be considered by policymakers in the EECA region. Using insights from current implementations to scale up, plan operational changes and reallocate savings from mSTR could greatly enhance TB services and patient care.